Copper Thiophosphate (Cu3PS4) as Electrode for Sodium‐Ion Batteries with Ether Electrolyte. (13th March 2020) - Brehm, Wolfgang; Santhosha, Aggunda L.; Zhang, Zhenggang; Neumann, Christof; Turchanin, Andrey; Martin, Andréa; Pinna, Nicola; Seyring, Martin; Rettenmayr, Markus; Buchheim, Johannes R.; Adelhelm, Philipp
Abstract: Lithium and sodium thiophosphates (and related compounds) have recently attracted attention because of their potential use as solid electrolytes in solid‐state batteries. These compounds, however, exhibit only limited stability in practice as they react with the electrodes. The decomposition products partially remain redox active hence leading to excess capacity. The redox activity of thiophosphates is explicitly used to act as electrode for sodium‐ion batteries. Copper thiophosphate (Cu3 PS4 ) is used as a model system. The storage behavior between 0.01 and 2.5 V versus Na + /Na is studied in half cells using different electrolytes with 1 m NaPF6 in diglyme showing the best result. Cu3 PS4 shows highly reversible charge storage with capacities of about 580 mAh g −1 for more than 200 cycles @120 mA g −1 and about 450 mAh g −1 for 1400 cycles @1 A g −1 . The redox behavior is studied by operando X‐ray diffraction and X‐ray photoelectron spectroscopy. During initial sodiation, Cu3 PS4 undergoes a conversion reaction including the formation of Cu and Na2 S. During cycling, the redox activity seems dominated by sulfur. Interestingly, the capacity of Cu3 PS4 for lithium storage is smaller, leading to about 170 mAh g −1 after 200 cycles. The results demonstrate that thiophosphates can lead to reversible charge storage over several hundred cycles without any notable capacity decay. Abstract : The application of a thiophosphate (Cu3 PS4 ) as an electrode material is demonstrated for sodium‐ion batteries in half cells. During cycling, the redox activity of Cu3 PS4 is found to be largely dominated by sulfur, including formation of Na2 S as a final discharge product. This way, Cu3 PS4 shows an excellent cycle life while reaching capacities of about 580 mAh g −1 .